2012
DOI: 10.1111/j.1533-2500.2012.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact and Burden of Chronic Pain in the Workplace: A Qualitative Systematic Review

Abstract: The body of evidence identified from the systematic review indicates that CP has a substantial negative impact on work-related outcomes, supporting the importance of interventions to reduce the burden of CP. Well-designed prospective studies specifically assessing the direct consequences of CP on employment are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
94
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 54 publications
(181 reference statements)
0
94
1
2
Order By: Relevance
“…The result was quite the opposite in earlier studies carried out in other European countries only on people in employment, in which pain made them unable to work [22]. Therefore the results can be interpreted in the specific context of the labour market in Poland, and the fact that the study was carried out on two sample groups.…”
Section: Discussioncontrasting
confidence: 37%
“…The result was quite the opposite in earlier studies carried out in other European countries only on people in employment, in which pain made them unable to work [22]. Therefore the results can be interpreted in the specific context of the labour market in Poland, and the fact that the study was carried out on two sample groups.…”
Section: Discussioncontrasting
confidence: 37%
“…In addition, another variable reporting "at least one type of chronic pain" was also tested. To explore whether the number of days absent from work varied according to the presence of each chronic pain 5] or at least 1 chronic pain, multinomial logistic regression models were performed. With this in mind, the dependent variable "number of days absent from work" was divided into 4 categories: none (reference category), 1 to 7, 8 to 30, and more than 30 days absent from work.…”
Section: Discussionmentioning
confidence: 99%
“…5 In Spain, Langley et al 6 found that subjects with chronic pain were absent from work 40% more frequently and were 30% more likely to report a lack of productivity than those without this symptom. However, that study was based on an Internet sample and, therefore, the conclusions may not be applicable to all work categories of the general population of Spain.…”
mentioning
confidence: 99%
“…Furthermore, good resources on the impact of pain on work 7 , costs 8 , and the patient experience 9 are already available in the literature. Nonetheless, it is important to continue to have up-to-date and precise estimates of these effects from multiple sources as a means of further understanding the complex nature of the relationship between pain severity and health outcomes.…”
Section: Introductionmentioning
confidence: 99%